1993
DOI: 10.1128/aem.59.12.4096-4100.1993
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Chlorine and Heat on the Survival of Hartmannella vermiformis and Subsequent Growth of Legionella pneumophila

Abstract: HartmanneUla vermiformis, a common amoebal inhabitant of potable-water systems, supports intracellular multiplication of Legionela pneumophila and is probably important in the transportation and amplification of legionellae within these systems. To provide a practical guide for decontamination of potable-water systems, we assessed the chlorine and heat resistance ofH. verrniformis. H. vermiformnis cysts and trophozoites were treated independently with chlorine at concentrations of 2.0 to 10.0 ppm for 30 min an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
1
2

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 17 publications
3
47
1
2
Order By: Relevance
“…Legionella are relatively resistant to conventional chlorination (Kuchta et al, 1993). Legionella spp.…”
Section: Detection and Disinfectionmentioning
confidence: 99%
“…Legionella are relatively resistant to conventional chlorination (Kuchta et al, 1993). Legionella spp.…”
Section: Detection and Disinfectionmentioning
confidence: 99%
“…Hartmannella vermiformis was more resistant to chlorine than any of the Candida spp. tested certainly due to its ability to form cysts with a double wall (Kuchta et al, 1993;Greub & Raoult, 2004). Chlorine doses of 3 and 6 lg mL À1 had no effect, compared with control ('0 lg mL À1 ', hatched).…”
Section: Chlorine Treatmentmentioning
confidence: 99%
“…Microscopic observations showed that amoebae resistant to H 2 O 2 at 9000 lg mL À1 were in cyst form (data not shown). Cysts are well known to be less vulnerable than trophozoites (Kuchta et al, 1993;Greub & Raoult, 2004).…”
Section: Hydrogen Peroxide Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Trophozoites and cysts of Hartmannella vermiformis may survive at 4 mg l )1 of chlorine treatment and still support intracellular multiplication and growth of Leg. pneumophila (Kuchta et al 1993). Similarly, cysts of Acanthamoeba castellanii and Acanthamoeba polyphaga can retain their viability at 10 mg l )1 of chlorination (Kilvington and Price 1990;Storey et al 2004).…”
Section: Introductionmentioning
confidence: 97%